Detection of KPC directly from positive blood cultures by MALDI-TOF: From research to the clinical microbiology laboratory routine - Moreira, Natália Kehl; Wilhelm, Camila Mörschbächer; da Silva Collar, Gabriela; Echevarria, Aymê Duarte; Becker, Júlia; Barth, Afonso Luís; Caierão, Juliana (Journal of microbiological methods, 2024)
Bloodstream infections (BSI) caused by carbapenem-resistant Gram-negative bacilli (CR-GNB) are a subject of major clinical concern, mainly those associated with carbapenemase-producing isolates. Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) has been proposed to detect specific β-lactamases, including KPC. We aimed to detect KPC enzyme directly from positive blood cultures using MALDI-TOF MS. Overall, 146 clinical Gram-negative bacilli (46 CR-GNB) recovered from consecutive blood cultures were evaluated. Proteins were extracted using formic acid, isopropyl alcohol, and water and spotted onto a steel target plate using the double-layer sinapinic acid method. The relative ions intensity ≥120 arbitrary units (a.u.) of a peak close to 28,700 m/z indicated the presence of KPC. The results were compared to HRM-qPCR methodology. This specific peak was observed in 11/14 blood bottles with blaKPC positive isolates (78.6% sensitivity), with 3 false-positive results (97.7% specificity). Analysis from colonies reached identical sensitivity (78.6%), but higher specificity (100%). The detection of KPC peaks directly from positive blood cultures using MALDI-TOF MS is feasible and rapid. It's excellent specificity indicates that positive results are consistently associated with the presence of a KPC producer in positive blood culture. •Bloodstream infections caused by carbapenem-resistant Gram-negative bacilli are associated with high mortality.•The early initiation of appropriate antimicrobial therapy improves patient prognosis.•Klebsiella pneumoniae carbapenemase is endemic in many geographical regions.•Rapid methodologies to detect specific mechanisms of resistance are needed.